A kind of high thermal conductivity aramid composite insulation paper for electric power equipment, preparation method and application
By modifying silver nanoparticles on the upper surface of aramid nanofibers and combining them with boron nitride nanosheets to form a thermal conductivity channel, the problem of insufficient thermal conductivity of traditional aramid insulating paper is solved, and the improvement of high thermal conductivity and mechanical properties is achieved. In terms of the cooling requirements of electrical equipment.
Patent Information
- Application Number
- CN202410962625.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-18
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-07-18
AI Technical Summary
Traditional aramid insulating paper has insufficient thermal conductivity, which cannot meet the heat dissipation needs of electrical equipment, and it is difficult to improve thermal conductivity by improving its molecular and link structure.
A composite material of aramid nanofibers and silver nitrate and boron nitride nanosheets is used to modify the uniform distribution of silver nanoparticles and boron nitride nanosheets to form a dense brick mud structure and improve thermal conductivity.
It significantly improves the thermal conductivity of insulating paper and maintains good mechanical properties, making it suitable for large-scale production.
Smart Images

Figure CN118563588B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of insulating materials, and in particular to a high thermal conductivity aramid composite insulating paper for electric power equipment, a preparation method and an application thereof. Background Art
[0002] With the rapid development of ultra-high voltage and UHV technologies, small-volume AC variable frequency motors and other equipment have been widely used in various complex projects. Under high voltage and high frequency working environments, the heat generated by electrical equipment accumulates rapidly and cannot be discharged in time, and the heat accumulated in the coils of electrical equipment cannot be transferred to the heat dissipation equipment or insulating oil in time, thus damaging the insulation system of the electrical equipment and seriously shortening its service life.
[0003] As the main insulating material in electrical equipment, aramid insulation paper has a key influence on improving the heat dissipation capacity of the insulation system. However, as a polymer insulation material, aramid fiber itself is a poor conductor of heat, with a thermal conductivity of less than 0.2 W / (m·K), so traditional aramid insulation paper cannot meet the heat dissipation requirements of electrical equipment. At the same time, the high rigidity structure and high crystallinity lead to high chemical and thermal stability of aramid, making it difficult to improve the thermal conductivity of aramid insulation paper by changing its molecular and chain structure. Summary of the invention
[0004] In view of the problems existing in the prior art, a high thermal conductivity aramid composite insulation paper for power equipment, a preparation method and application are provided.
[0005] The technical solution adopted by the present invention is: a method for preparing high thermal conductivity aramid composite insulation paper for power equipment, comprising the following steps:
[0006] Step 1: Aramid nanofibers and silver nitrate are mixed and dissolved in a solvent at a mass ratio of 1:0.05-2, dispersed, and then tannic acid is added for reduction reaction to obtain aramid nanofibers with surface modified silver nanoparticles;
[0007] Step 2: mixing the aramid nanofibers with surface modified silver nanoparticles obtained in step 1 and the boron nitride nanosheets at a mass ratio of 1-2:0.1-0.4, and slurrying to obtain a composite slurry;
[0008] Step 3: The composite slurry obtained in step 2 is subjected to vacuum filtration to form a film and hot pressing to obtain composite insulating paper.
[0009] Furthermore, the preparation method of the aramid nanofiber is as follows:
[0010] Ultrasonic treatment, cleaning and drying of para-aramid fibers;
[0011] Para-aramid fibers are treated with plasma;
[0012] The treated para-aramid fibers are stripped using an alkaline solution to obtain aramid nanofibers;
[0013] The processing parameters used in the plasma treatment are as follows:
[0014] The power is 200 W, the vacuum degree is 100 Pa, and the treatment is carried out under a protective atmosphere;
[0015] During the alkaline solution treatment process: the alkaline solution is a potassium hydroxide solution with a concentration of 0.3 g / L.
[0016] Furthermore, the preparation method of the boron nitride nanosheets in step 2 is as follows:
[0017] Hexagonal boron nitride and lithium citrate in a mass ratio of 1:1 are dissolved in a solvent and mixed, and then subjected to ultrasonic treatment after being fully dispersed;
[0018] Exfoliated boron nitride nanosheets were obtained after treatment at 180 °C for 6 h.
[0019] Furthermore, the preparation process of the aramid nanofibers with surface modified silver nanoparticles in step 1 is as follows:
[0020] The silver nitrate solution is ultrasonically dispersed, mixed with the aramid nanofibers, and then ultrasonically treated;
[0021] Tannic acid was added and treated at 60 °C for 3 h to obtain aramid nanofibers with surface modified silver nanoparticles.
[0022] Furthermore, in step 2, high-speed shear mixing and slurrying is performed, and the high-speed shear rate is 10000-15000 rpm and the time is 15 min.
[0023] Furthermore, in step 3, hot pressing is performed at 175-195° C. and a pressure of 20 MPa.
[0024] Furthermore, in step 1, the aramid nanofibers are obtained by stripping para-aramid fibers, and have a diameter of 10 to 50 nm and a length greater than 3 μm; the diameter of the nanosilver particles is 30 to 50 nm.
[0025] Furthermore, the boron nitride nanosheets are obtained by exfoliation of hexagonal boron nitride through ultrasonic and hydrothermal treatment, and have a particle size of 150 to 250 nm and a thickness of less than 5 nm.
[0026] A high thermal conductivity aramid composite insulating paper, wherein the composite insulating paper is a dense brick-mud structure formed by using aramid nanofibers with surface modified silver nanoparticles as a skeleton network and using boron nitride nanosheets as a thermal conductive filler.
[0027] An application of high thermal conductivity aramid composite insulation paper, wherein the high thermal conductivity composite insulation paper is used in a variable frequency motor.
[0028] The beneficial effects of the present invention are:
[0029] (1) Compared with the existing insulation paper, the high thermal conductivity aramid composite insulation paper obtained by the present invention has significantly improved thermal conductivity and good mechanical properties;
[0030] (2) The preparation method of the present invention is simple, low-cost and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the reaction principle of the present invention.
[0032] Figure 2 Schematic diagram of the thermal conductivity and thermal conductivity increment of the composite insulating paper obtained in Comparative Example 1 and Examples 1 to 4. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0034] like Figure 1 As shown, a method for preparing high thermal conductivity aramid composite insulation paper for power equipment comprises the following steps:
[0035] Step 1: Aramid nanofibers and silver nitrate are mixed and dissolved in a solvent at a mass ratio of 1:0.05-2, dispersed, and then tannic acid is added for reduction reaction to obtain aramid nanofibers with surface modified silver nanoparticles;
[0036] The preparation method of aramid nanofiber is as follows:
[0037] The para-aramid fiber was immersed in an acetone solution and ultrasonically treated for 48 h, the acetone was fully washed with ethanol, and vacuum dried at 60 °C for 24 h before being sealed and stored.
[0038] The para-aramid fiber was treated by plasma at a power of 200 W and a vacuum degree of 100 Pa under a protective atmosphere. The protective atmosphere was argon, and argon was introduced for 6 min before treatment at a flow rate of 30 mL / min.
[0039] The treated para-aramid fibers were stripped with an alkaline solution, and the para-aramid fibers were mixed with potassium hydroxide and dimethyl sulfoxide in a ratio of 1 g:1.5 g:500 mL and sealed, and mechanically stirred at 1000 rpm for 14 days at room temperature. Aramid nanofibers stably dispersed in the potassium hydroxide / dimethyl sulfoxide system were obtained; the diameter was 10-50 nm and the length was greater than 3 μm.
[0040] Among them, the plasma treatment of para-aramid fiber increases the polar groups such as hydroxyl, carboxyl, oxygen free radical, and peroxy free radical on the fiber surface, without changing the internal properties of the fiber. At the same time, it increases the active sites on the fiber surface, making it easy to combine with particles in the solution. The roughness of the surface of the aramid fiber after plasma etching has been greatly improved, and relatively obvious grooves have been produced on the surface, increasing the contact area between the fiber and the strong alkali. At the same time, the high strength, high temperature resistance and excellent insulation properties of the original aramid fiber are retained.
[0041] The preparation process of aramid nanofibers with surface modified silver nanoparticles is as follows:
[0042] Silver nitrate was added to deionized water and ultrasonically treated for 30 min. The aramid nanofibers obtained by plasma treatment and silver nitrate were mixed to obtain a mixed solution, which was ultrasonically treated for 15 min.
[0043] Tannic acid solution was added and treated at 60 °C for 3 h to obtain aramid nanofibers with surface modified silver nanoparticles, wherein the diameter of the silver nanoparticles was 30 nm to 50 nm, and the mass ratio of tannic acid to aramid nanofibers was 3:2. The mass ratio of aramid nanofibers to silver nanoparticles in the aramid nanofibers with surface modified silver nanoparticles was 1:0.05 to 0.2.
[0044] Among them, nanosilver particles have high reactivity, are easy to disperse and convenient to compound with other materials. The silver nanoparticles obtained by in situ reduction of silver nitrate on the surface of aramid nanofibers are evenly attached to the fiber surface, acting as "welding points" between the aramid nanofibers and boron nitride nanosheets, constructing an effective heat conduction channel, which is conducive to the rapid dissipation of heat.
[0045] Step 2: The aramid nanofibers with surface modified silver nanoparticles obtained in step 1 and the boron nitride nanosheets are mixed in a mass ratio of 1 to 2:0.1 to 0.4, and slurry is made to obtain a composite slurry; the slurry is made by high-speed shear mixing, and the high-speed shear rate is 10,000 to 15,000 rpm for 15 minutes. When the aramid nanofibers and the boron nitride nanosheets are mixed in the above mass ratio, the boron nitride nanosheets are uniformly deposited in the aramid nanofiber matrix, presenting a dense brick mud structure. When the mass ratio of the two exceeds the above range and increases to 0.3, the boron nitride nanosheets aggregate in the aramid nanofiber matrix, the interface thermal resistance increases, and the heat conduction is hindered.
[0046] The preparation method of boron nitride nanosheets is as follows:
[0047] Hexagonal boron nitride and lithium citrate in a mass ratio of 1:1 were dissolved in a solvent (isopropanol and deionized water were mixed in a volume ratio of 3:1), mixed, and then fully stirred and treated with an ultrasonic disperser for 15 min and ultrasonic treatment for 6 h.
[0048] After treatment at 180 °C for 6 h, the exfoliated boron nitride nanosheets were obtained, with a particle size of 150-250 nm and a thickness of less than 5 nm. The exfoliated boron nitride nanosheets were repeatedly and thoroughly washed with deionized water to remove the lithium citrate remaining on the surface of the boron nitride nanosheets. The high-speed centrifugation speed was 10,000 rpm, and the obtained boron nitride nanosheet powder was freeze-dried for 48 h. The boron nitride nanosheets exfoliated by ultrasound and hydrothermal reaction were thin, small in size, and not easy to aggregate, and the exfoliation effect was good.
[0049] During the ultrasonic stripping process, a large number of hydroxyl groups were introduced on the surface of the boron nitride nanosheets, making them well dispersed in the aramid nanofibers. As a thermal conductive filler, they were evenly mixed with the aramid nanofibers to improve the thermal conductivity of the composite insulating paper. At the same time, the boron nitride nanosheets were evenly deposited in the aramid nanofibers to form a dense brick-mud structure, which improved the mechanical strength of the insulating paper.
[0050] Step 3: The composite slurry obtained in step 2 is subjected to vacuum filtration to form a membrane and hot pressing to obtain composite insulating paper. The hot pressing is carried out at 175-195° C. and a pressure of 20 MPa.
[0051] First, prepare the vacuum filtration equipment, assemble the filtration device, install the filter membrane on the filter head, seal it, install the filtration bottle, and connect the vacuum pump unit. Start the unit to generate vacuum and check whether all pipelines are sealed. Transfer the mixed slurry to the filtration bottle and start the vacuum pump to filter until the film is formed.
[0052] Vacuum filtration is beneficial to the directional distribution of boron nitride nanosheets in aramid nanofibers to form a continuous thermal conductive bridge. At the same time, silver nanoparticles increase the effective thermal conductive channels, which helps the conduction and dissipation of heat, significantly improving the thermal conductivity of the composite insulation paper and thus improving its thermal conductivity.
[0053] The composite insulating paper obtained by the invention has a dense brick-mud structure formed by using aramid nanofibers with surface modified silver nanoparticles as a skeleton network and boron nitride nanosheets as a thermal conductive filler. The silver nanoparticles act as "welding points" between the aramid nanofibers and the boron nitride nanosheets to form an effective thermal conductive channel.
[0054] Example 1
[0055] A method for preparing high thermal conductivity aramid composite insulation paper for power equipment comprises the following steps:
[0056] Step 1: Preparation of aramid nanofibers modified with silver nanoparticles
[0057] First, prepare aramid nanofibers
[0058] The para-aramid fiber was immersed in an acetone solution and ultrasonically treated for 48 h. The acetone was fully washed with ethanol, and then vacuum dried at 60 °C for 24 h and sealed.
[0059] The treated para-aramid fiber was placed in a low-temperature plasma treatment instrument, with a power of 200 W, a vacuum degree of 100 Pa, and argon gas for 6 min at a flow rate of 30 mL / min. The plasma-treated para-aramid fiber was placed in a sealed container with potassium hydroxide and dimethyl sulfoxide in a ratio of 1 g:1.5 g:500 mL, and mechanically stirred at 1000 rpm for 14 days at room temperature to obtain aramid nanofibers stably dispersed in the potassium hydroxide / dimethyl sulfoxide system.
[0060] Aramid nanofibers modified with nanosilver particles were prepared by tannic acid reduction reaction using aramid nanofibers as support carriers: 1 g of silver nitrate was added to 100 mL of deionized water, and ultrasonic treatment was performed for 30 min. The plasma-treated aramid nanofibers and silver nitrate were mixed at a mass ratio of 1:0.05 to obtain a mixed solution. Ultrasonic treatment was performed for 15 min, and 300 mL of 0.1 g / mL tannic acid solution was added and reacted at 60 °C for 3 h to obtain aramid nanofibers modified with nanosilver particles.
[0061] Step 2: Preparation of composite slurry of aramid nanofibers and boron nitride nanosheets with surface modified silver nanoparticles
[0062] Boron nitride nanosheets were obtained by ultrasonic and hydrothermal treatment:
[0063] 1 g of hexagonal boron nitride and 1 g of lithium citrate were added to 100 mL of a mixed solution of isopropanol and deionized water in a volume ratio of 3:1, stirred thoroughly, treated with an ultrasonic disperser for 15 min, then ultrasonically treated for 6 h, and transferred to an autoclave.
[0064] The boron nitride nanosheets after being treated at 180 °C for 6 h were vitrified, and the lithium citrate remaining on the surface of the boron nitride nanosheets was repeatedly and thoroughly washed with deionized water. The high-speed centrifugation speed was 10,000 rpm, and the obtained boron nitride nanosheet powder was freeze-dried for 48 h.
[0065] The aramid nanofibers and boron nitride nanosheets surface-modified with nano-silver particles were fully mixed with deionized water at a mass ratio of 1:0.2:500, and the high-speed shear rate was 10000 rpm. The treatment time was 15 min to obtain a composite slurry.
[0066] Step 3: The composite slurry obtained in step 2 is subjected to vacuum filtration to form a film and hot pressing to obtain composite insulating paper.
[0067] First, assemble the filtration device, install the filter membrane on the filter head, seal it, install the suction bottle, and connect the vacuum pump unit. Start the unit to generate vacuum, check whether all pipelines are sealed, transfer the composite slurry to the suction bottle, start the vacuum pump and filter for 12 hours until the membrane is formed.
[0068] The film was hot-pressed by a vacuum hot press at 20 MPa and 180 °C to obtain a high thermal conductivity aramid composite insulation paper. The thermal conductivity coefficient of the composite insulation paper was tested to be 2.6 W / (m·K).
[0069] Example 2
[0070] The other steps of this embodiment are the same as those of embodiment 1, except that the mass ratio of aramid nanofiber to silver nitrate is 1:0.1 in step 1. The thermal conductivity of the composite insulating paper is tested to be 4.5 W / (m·K).
[0071] Example 3
[0072] The other steps of this embodiment are the same as those of embodiment 1, except that the mass ratio of aramid nanofiber to silver nitrate is 1:0.15 in step 1. The thermal conductivity of the composite insulating paper is tested to be 8.3 W / (m·K).
[0073] Example 4
[0074] The other steps of this embodiment are the same as those of embodiment 1, except that the mass ratio of aramid nanofiber to silver nitrate is 1:0.2 in step 1. The thermal conductivity of the composite insulating paper is tested to be 11.4 W / (m·K).
[0075] The thermal conductivity and thermal conductivity increment of the composite insulating paper obtained in Examples 1 to 4 and Comparative Example 1 are as follows: Figure 2 As shown in the figure, it can be seen that as the content of nano-silver particles increases, the thermal conductivity of the insulation paper increases accordingly.
[0076] Example 5
[0077] The other steps of this embodiment are the same as those of Embodiment 1, except that in Step 2, the mass ratio of aramid nanofiber to silver nitrate is 1:0.25.
[0078] Example 6
[0079] A method for preparing high thermal conductivity aramid composite insulation paper for power equipment comprises the following steps:
[0080] Step 1: Preparation of aramid nanofibers modified with silver nanoparticles
[0081] First, prepare aramid nanofibers
[0082] The para-aramid fiber was immersed in an acetone solution and ultrasonically treated for 48 h. The acetone was fully washed with ethanol, and then vacuum dried at 60 °C for 24 h and sealed.
[0083] The treated para-aramid fiber was placed in a low-temperature plasma treatment instrument, with a power of 200 W, a vacuum degree of 100 Pa, and argon gas for 6 min at a flow rate of 30 mL / min. The plasma-treated para-aramid fiber was placed in a sealed container with potassium hydroxide and dimethyl sulfoxide in a ratio of 1 g:1.5 g:500 mL, and mechanically stirred at 1000 rpm for 14 days at room temperature to obtain aramid nanofibers stably dispersed in the potassium hydroxide / dimethyl sulfoxide system.
[0084] Aramid nanofibers modified with nanosilver particles were prepared by tannic acid reduction reaction using aramid nanofibers as support carriers: 1 g of silver nitrate was added to 100 mL of deionized water, ultrasonically treated for 30 min, and the plasma-treated aramid nanofibers and silver nitrate were mixed at a mass ratio of 1:0.2 to obtain a mixed solution. After ultrasonic treatment for 15 min, 300 mL of 0.1 g / mL tannic acid solution was added and reacted at 60 °C for 3 h to obtain aramid nanofibers modified with nanosilver particles.
[0085] Step 2: Preparation of composite slurry of aramid nanofibers and boron nitride nanosheets with surface modified silver nanoparticles
[0086] Boron nitride nanosheets were obtained by ultrasonic and hydrothermal treatment:
[0087] 1 g of hexagonal boron nitride and 1 g of lithium citrate were added to 100 mL of a mixed solution of isopropanol and deionized water in a volume ratio of 3:1, stirred thoroughly, treated with an ultrasonic disperser for 15 min, then ultrasonically treated for 6 h, and transferred to an autoclave.
[0088] The boron nitride nanosheets after being treated at 180 °C for 6 h were vitrified, and the lithium citrate remaining on the surface of the boron nitride nanosheets was repeatedly and thoroughly washed with deionized water. The high-speed centrifugation speed was 10,000 rpm, and the obtained boron nitride nanosheet powder was freeze-dried for 48 h.
[0089] The aramid nanofibers and boron nitride nanosheets surface-modified with nanosilver particles were fully mixed with deionized water at a mass ratio of 1:0.2:500, the high-speed shear rate was 15000 rpm, and the processing time was 15 min to obtain a composite slurry.
[0090] Step 3: The composite slurry obtained in step 2 is subjected to vacuum filtration to form a film and hot pressing to obtain composite insulating paper.
[0091] First, assemble the filtration device, install the filter membrane on the filter head, seal it, install the suction bottle, and connect the vacuum pump unit. Start the unit to generate vacuum, check whether all pipelines are sealed, transfer the composite slurry to the suction bottle, start the vacuum pump and filter for 12 hours until the membrane is formed.
[0092] The film was hot-pressed by a vacuum hot press at 20 MPa and 175 °C to obtain a high thermal conductivity aramid composite insulating paper.
[0093] Example 7
[0094] A method for preparing high thermal conductivity aramid composite insulation paper for power equipment comprises the following steps:
[0095] Step 1: Preparation of aramid nanofibers modified with silver nanoparticles
[0096] First, prepare aramid nanofibers
[0097] The para-aramid fiber was immersed in an acetone solution and ultrasonically treated for 48 h. The acetone was fully washed with ethanol, and then vacuum dried at 60 °C for 24 h and sealed.
[0098] The treated para-aramid fiber was placed in a low-temperature plasma treatment instrument, with a power of 200 W, a vacuum degree of 100 Pa, and argon gas for 6 min at a flow rate of 30 mL / min. The plasma-treated para-aramid fiber was placed in a sealed container with potassium hydroxide and dimethyl sulfoxide in a ratio of 1 g:1.5 g:500 mL, and mechanically stirred at 1000 rpm for 14 days at room temperature to obtain aramid nanofibers stably dispersed in the potassium hydroxide / dimethyl sulfoxide system.
[0099] Aramid nanofibers modified with nanosilver particles were prepared by tannic acid reduction reaction using aramid nanofibers as support carriers: 1 g of silver nitrate was added to 100 mL of deionized water, and ultrasonic treatment was performed for 30 min. The plasma-treated aramid nanofibers and silver nitrate were mixed at a mass ratio of 1:0.05 to obtain a mixed solution. Ultrasonic treatment was performed for 15 min, and 300 mL of 0.1 g / mL tannic acid solution was added and reacted at 60 °C for 3 h to obtain aramid nanofibers modified with nanosilver particles.
[0100] Step 2: Preparation of composite slurry of aramid nanofibers and boron nitride nanosheets with surface modified silver nanoparticles
[0101] Boron nitride nanosheets were obtained by ultrasonic and hydrothermal treatment:
[0102] 1 g of hexagonal boron nitride and 1 g of lithium citrate were added to 100 mL of a mixed solution of isopropanol and deionized water in a volume ratio of 3:1, stirred thoroughly, treated with an ultrasonic disperser for 15 min, then ultrasonically treated for 6 h, and transferred to an autoclave.
[0103] The boron nitride nanosheets after being treated at 180 °C for 6 h were vitrified, and the lithium citrate remaining on the surface of the boron nitride nanosheets was repeatedly and thoroughly washed with deionized water. The high-speed centrifugation speed was 10,000 rpm, and the obtained boron nitride nanosheet powder was freeze-dried for 48 h.
[0104] The aramid nanofibers and boron nitride nanosheets surface-modified with nanosilver particles were fully mixed with deionized water at a mass ratio of 1:0.2:500, and the high-speed shear rate was 13000 rpm. The processing time was 15 min to obtain a composite slurry.
[0105] Step 3: The composite slurry obtained in step 2 is subjected to vacuum filtration to form a film and hot pressing to obtain composite insulating paper.
[0106] First, assemble the filtration device, install the filter membrane on the filter head, seal it, install the suction bottle, and connect the vacuum pump unit. Start the unit to generate vacuum, check whether all pipelines are sealed, transfer the composite slurry to the suction bottle, start the vacuum pump and filter for 12 hours until the membrane is formed.
[0107] The film was hot-pressed by a vacuum hot press at 20 MPa and 195 °C to obtain a high thermal conductivity aramid composite insulation paper.
[0108] Comparative Example
[0109] Prepare the insulating paper as follows:
[0110] Step 1: Preparation of composite slurry of aramid nanofibers and boron nitride nanosheets
[0111] Boron nitride nanosheets were obtained by ultrasonic and hydrothermal treatment:
[0112] 1 g of hexagonal boron nitride and 1 g of lithium citrate were added to 100 mL of a mixed solution of isopropanol and deionized water in a volume ratio of 3:1, stirred thoroughly, treated with an ultrasonic disperser for 15 min, then ultrasonically treated for 6 h, and transferred to an autoclave.
[0113] The boron nitride nanosheets after being treated at 180 °C for 6 h were vitrified, and the lithium citrate remaining on the surface of the boron nitride nanosheets was repeatedly and thoroughly washed with deionized water. The high-speed centrifugation speed was 10,000 rpm, and the obtained boron nitride nanosheet powder was freeze-dried for 48 h.
[0114] Aramid nanofibers, boron nitride nanosheets and deionized water were fully mixed at a mass ratio of 1:0.2:500, the high-speed shear rate was 13000 rpm, and the processing time was 15 min to obtain a composite slurry.
[0115] Step 2: The composite slurry obtained in step 1 is subjected to vacuum filtration to form a film and hot pressing to obtain composite insulating paper.
[0116] First, assemble the filtration device, install the filter membrane on the filter head, seal it, install the suction bottle, and connect the vacuum pump unit. Start the unit to generate vacuum, check whether all pipelines are sealed, transfer the composite slurry to the suction bottle, start the vacuum pump and filter for 12 hours until the membrane is formed.
[0117] The film was hot-pressed by a vacuum hot press at 20 MPa and 195°C to obtain aramid composite insulation paper. The thermal conductivity coefficient of the composite insulation paper was tested to be 1.9 W / (m·K).
[0118] The present invention aims at the problem that the thermal conductivity of aramid insulation paper is low and cannot meet the heat dissipation requirements of current electrical equipment. The present invention adopts a chemical reduction method to load nano silver particles with high reactivity and easy bonding onto aramid nano fibers, and simultaneously adds boron nitride nano sheets. The nano silver particles, the boron nitride nano sheets and the aramid nano fibers are connected together to form an effective heat conduction channel. The interfacial thermal resistance of the composite aramid insulation paper can be reduced, thereby improving its thermal conductivity. Through vacuum filtration, an aramid composite insulation paper with uniformly distributed fillers and high thermal conductivity is obtained.
Claims
1. A method for preparing high thermal conductivity aramid composite insulation paper for power equipment, It is characterized in that The following steps are involved: Step 1: Aramid nanofibers and silver nitrate are mixed and dissolved in a solvent at a mass ratio of 1:0.05-2, dispersed, and then tannic acid is added for reduction reaction to obtain aramid nanofibers with surface modified silver nanoparticles; Step 2: The aramid nanofibers with surface modified silver nanoparticles obtained in step 1 and the boron nitride nanosheets are mixed in a mass ratio of 1-2:0.1-0.4, and slurried to obtain a composite slurry; the preparation method of the boron nitride nanosheets is as follows: Hexagonal boron nitride and lithium citrate in a mass ratio of 1:1 are dissolved in a solvent and mixed, and then subjected to ultrasonic treatment after being fully dispersed; After treatment at 180 °C for 6 h, exfoliated boron nitride nanosheets were obtained; Step 3: The composite slurry obtained in step 2 is subjected to vacuum filtration to form a film and hot pressing to obtain composite insulating paper.
2. A method for preparing a high thermal conductivity aramid composite insulation paper for electric power equipment according to claim 1, It is characterized in that The preparation method of the aramid nanofiber is as follows: Ultrasonic treatment, cleaning and drying of para-aramid fibers; Para-aramid fibers are treated with plasma; The treated para-aramid fibers are stripped using an alkaline solution to obtain aramid nanofibers; The processing parameters used in the plasma treatment are as follows: The power is 200W, the vacuum degree is 100Pa, and the treatment is carried out under a protective atmosphere; During the alkaline solution treatment process: the alkaline solution is a potassium hydroxide solution with a concentration of 0.3 g / L.
3. A method for preparing a high thermal conductivity aramid composite insulation paper for electric power equipment according to claim 1, It is characterized in that The preparation process of the aramid nanofibers with surface modified silver nanoparticles in step 1 is as follows: The silver nitrate solution is ultrasonically dispersed, mixed with the aramid nanofibers, and then ultrasonically treated; Tannic acid was added and treated at 60°C for 3 hours to obtain aramid nanofibers with surface modified silver nanoparticles.
4. The method for preparing the high thermal conductivity aramid composite insulation paper for electric power equipment according to claim 1, It is characterized in that In step 2, high-speed shear mixing and slurrying are adopted, and the high-speed shear rate is 10000-15000rpm, and the time is 15min.
5. The method for preparing the high thermal conductivity aramid composite insulation paper for electric power equipment according to claim 1, It is characterized in that In step 3, hot pressing is performed at 175-195° C. and a pressure of 20 MPa.
6. The method for preparing a high thermal conductivity aramid composite insulation paper for electric power equipment according to claim 1, It is characterized in that In the step 1, the aramid nanofibers are obtained by stripping para-aramid fibers, and have a diameter of 10 to 50 nm and a length greater than 3 μm; the diameter of the nanosilver particles is 30 to 50 nm.
7. The method for preparing a high thermal conductivity aramid composite insulation paper for electric power equipment according to claim 1, It is characterized in that The boron nitride nanosheet is obtained by exfoliating hexagonal boron nitride through ultrasonic and hydrothermal treatment, and has a particle size of 150 to 250 nm and a thickness of less than 5 nm.
8. The high thermal conductivity aramid composite insulation paper for electric power equipment obtained by the preparation method according to any one of claims 1 to 7, It is characterized in that The composite insulating paper is a dense brick-mud structure formed by using aramid nanofibers with surface modified silver nanoparticles as a skeleton network and boron nitride nanosheets as a thermal conductive filler.
9. Application of the high thermal conductivity aramid composite insulation paper for power equipment as claimed in claim 8, It is characterized in that The high thermal conductivity aramid composite insulating paper is used in a variable frequency motor.
